Evaluation of two-microphone acoustic feedback cancellation using uniform and non-uniform sub-bands in hearing AIDS - Tran, Linh T.T.; Dam, Hai Huyen Heidi; Schepker, H.; Doclo, S.; Nordholm, Sven (2016)
The limiting feature of hearing aids is acoustic feedback. This feedback problem has been approached by using an acoustic feedback canceller. This well known identification in a loop problem, will give a biased solution due to correlation between the desired and loudspeaker signals. Speech and music signals have long tails in the correlation. As a result, the performance of the system is considerably degraded and under certain conditions the cancellation system will be unstable. The two-microphone techniques have the potential to significantly reduce this problem. This paper introduces the applications of uniform and non-uniform sub-band techniques into the two-microphone acoustic feedback cancellation (AFC-2mics) to decorrelate input signals and individually adapt solutions in those bands. The system has been evaluated in terms of Misalignment (MisAL) and Maximum Stable Gain (MSG) using both male and female speech input signals. The simulation results show that our proposed methods provide better performance than the other existing methods. © 2015 Asia-Pacific Signal and Information Processing Association.